On the implementation of a microgrid project with renewable distributed generation - Leite, V. (2014)
This paper describes the on-going implementation of a microgrid project with renewable distributed generation under the context of an initiative with demonstration purposes in an university campus. In the actual context of the electrical energy demand increase and limited conventional resources, along with the consciousness of the climate changes and the need to invest in clean energies, microgrids allows the integration of dispersed energy sources, mainly renewable, which make them cost effective, providing a viable alternative to centralized production, transmission and distribution system for remote community areas. The design concept of the microgrid and a description of the base equipment and energy sources already integrated are presented. From the on-going projects to be integrated on the microgrid, it is presented the Grid-to- Vehicle and Vehicle-to-Grid concept, which will provide a second energy storage element using the battery of an electric vehicle. To accomplish this objective, a bi-directional power converter is being developed and simulation results of its power structure and control are presented.